Artificial intelligence - Thomas, Peggy 1960-; Gale Group (Detroit, Mich. Lucent Books, 2005)
A factbook on the development and uses of intelligent robots that utilize artificial intelligence. An overview of how researchers simulate brain processes in these machines, and the variety of uses the machines/robots have. Written for young adults.
Introduction : fact follows fiction -- The first thinking machines -- Mind versus metal -- Everyday AI -- AI and robotics -- In pursuit of the mechanical man -- The future of AI.
Electronic reproduction.
Keywords: Artificial intelligence -- Juvenile literature; Electronic books